Assessing the Effect of Social Capital on Depression in Adults - Aulia Putri Nugraheni; Bhisma Murti; Argyo Demartoto (Masters Program in Public Health, 2025)
Background: Depression is a mental health problem that affects an individual's quality of life. Previous studies have shown that individuals with high social capital are less likely to experience depression. Understanding the dynamics of social capital and its impact on depression is essential for developing interventions and policies that can improve mental well-being at both the individual and community levels. This study aims to analyze the influence of structural, cognitive, and relational social capital on depression in adults.Subjects and Method: This study is a cross-sectional study carried out in Klaten, Central Java in September-October 2024. Population of 726,839 adults and a sample of 200 adults aged 19-59 years were selected using multistage random sampling. The dependent variable was depression. The independent variables were structural social capital, cognitive social capital, and relational social capital. Depression data was measured using Patient Health Questionnaire-9 (PHQ-9) and other data using questionnaires. Data was analyzed using the Structural Equation Model run on STATA 13.Results: Strong social capital lowered adults' risk of depression (b= -0.39; CI 95%= -0.56 to -0.23; p= 0.001). The older you get, the lower the depression score (b= -0.17; CI 95%= -0.31 to -0.03; p= 0.018). The social capital construct in this study is positively and statistically significant by the structural social capital component (b= 0.75; CI 95%= 0.58 to 0.92; p= 0.001), cognitive social capital component (b= 0.56; CI 95%= 0.39 to 0.73; p= 0.001), and the relational social capital component (b= 0.62; CI 95%= 0.48 to 0.76; p= 0.001). The SEM model showed a good fit (Chi-square p= 0.113; RMSEA= 0.070; CFI= 0.98; TLI= 0.93; SRMR= 0.03).Conclusion: Strong social capital and increasing age lower the risk of depression in adults. The social capital construct is positively and statistically significant by the components of structural social capital, cognitive social capital, and relational social capital. This SEM model shows a good fit.